Topological, chemical and electro-optical characteristics of riboflavin-doped artificial and natural DNA thin films. Issue 2 (14th February 2018) - Gnapareddy, Bramaramba; Dugasani, Sreekantha Reddy; Son, Junyoung; Park, Sung Ha
Abstract : DNA is considered as a useful building bio-material, and it serves as an efficient template to align functionalized nanomaterials. Riboflavin (RF)-doped synthetic double-crossover DNA (DX-DNA) lattices and natural salmon DNA (SDNA) thin films were constructed using substrate-assisted growth and drop-casting methods, respectively, and their topological, chemical and electro-optical characteristics were evaluated. The critical doping concentrations of RF ([RF]C, approx. 5 mM) at given concentrations of DX-DNA and SDNA were obtained by observing the phase transition (from crystalline to amorphous structures) of DX-DNA and precipitation of SDNA in solution above [RF]C . [RF]C are verified by analysing the atomic force microscopy images for DX-DNA and current, absorbance and photoluminescence (PL) for SDNA. We study the physical characteristics of RF-embedded SDNA thin films, using the Fourier transform infrared spectrum to understand the interaction between the RF and DNA molecules, current to evaluate the conductance, absorption to understand the RF binding to the DNA and PL to analyse the energy transfer between the RF and DNA. The current and UV absorption band of SDNA thin films decrease up to [RF]C followed by an increase above [RF]C . By contrast, the PL intensity illustrates the reverse trend, as compared to the current and UV absorption behaviour as a function of the varying [RF]. Owing to the intense PL characteristic of RF, the DNA lattices and thin films with RF might offer immense potential to develop efficient bio-sensors and useful bio-photonic devices.